Clinical, microbiological profile of dengue cases reported at a tertiary care hospital in Telangana, India - S.L., Annapoorna; Latha, M.L. Kavitha; Shanker, Shanker (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Dengue is the most common disease among all the arthropod borne viral diseases. Dengue viruses (DV) belong to the family Flaviviridae, and there are four serotypes of the virus referred to as DV-1, DV-2, DV-3, and DV-4 Dengue is the most common and widespread arboviral infection in the world today. It is an increasingly prevalent tropical arbovirus infection with significant morbidity and mortality. Materials and Methods: The study was carried out in the department of microbiology at Ronald Ross Institute of Tropical Diseases for a period of 6 years i.e. from January 2011 to December 2017. Blood was collected from each patient suspected to be suffering from dengue, at least 5 days after onset of fever. Serum was tested for the presence of dengue NS1 antigen and antihuman IgM antibodies using Panbio Dengue Early enzyme-linked immunosorbent assay (ELISA) kit and National Institute of Virology. Results: A total of 5181 samples were tested over a period of 7 years i.e. from 2011-2017. Out of which 1440 (27.79%) were sero-positive for dengue with symptoms of classical dengue fever. IgM in 1033(19.9%) NS1- 320(6.2%). A male preponderance was observed (905, 62.8%). Conclusion: As, during epidemic and nonepidemic years, dengue infections are mostly seen in post-monsoon season, hence preventive measures should be in full swing at the very onset of the monsoons